Selective arterial embolisation of bilateral angiomyolipomata in a symptomatic pregnant female. (20th November 2013) - Davis, Niall F; Kelly, Rory; Lee, Michael J; Mohan, Ponnusamy
Abstract : Renal angiomyolipoma (RA) is a rare benign tumour that can expand rapidly during pregnancy due to oestrogen and other hormonal factors. Complications associated with expanding renal angiomyolipomata are spontaneous retroperitoneal haemorrhage secondary to acute rupture and thrombosis of the renal vein or inferior vena cava. MRI is recommended for diagnostic purposes in pregnancy; however, this modality is not always readily available. In the present report, we describe the first case of bilateral selective arterial embolisation for renal angiomyolipomata presenting symptomatically in a previously healthy pregnant female.